Produção de etanol 2G a partir de hemicelulose de bagaço de cana-de-açúcar utilizando Saccharomyces cerevisiae selvagem e geneticamente modificada imobilizadas - Milessi, Thais Suzane dos Santos (Universidade Federal de São Carlos, 2017)
In ethanol production process from hemicellulosic fraction, the use of xylooligomers (XOS) as substrate reduce the contamination risk, favoring its application at industrial scale. Thus, a biocatalyst, containing xylanases, xylose isomerase (XI) and yeast co-immobilized in calcium alginate gel, was developed and XOS simultaneous hydrolysis, isomerization and fermentation (SHIF) process was studied. Firstly, xylanases from Multifect CX XL A03139 (XAS-5), a commercial enzyme preparation, and the recombinant xylanase from Bacillus subtilis (XynA) were selected to compose biocatalyst beads. XAS-5 presented better conversion (78.7%) and higher xylose production in the hydrolysis of beechwood xylan, while XynA showed exclusive endoxylanase activity. The immobilization and stabilization of XynA were performed in chitosan-glutaraldehyde, chitosan-glyoxyl and agarose-glyoxyl. Although the enzyme was efficiently immobilized on all supports, the agarose-glyoxyl-XynA derivative was notable for exhibiting remarkable stabilization under tested conditions (8600 times). Studies of SHIF process were carried out with birchwood xylan, leading to ethanol production (0.160 g/g and 0.092 g/L.h) and xylose accumulation, which indicated XI activity decrease. Further experiments were then performed to to identify possible inhibitors of XI (pH, Ca2+, Mg2+ and xylooligosaccharides). Ca2+ was identified as an inhibitor, while Mg2+ acts as an activator of the enzyme, and both actions are potentiated at acidic pHs. XI is also inhibited by XOS, with a decrease of 31.6% in XI activity in the presence of 7.0 g/L of xylobiose. For this reason, it was decided to evaluate SIF process with a recombinant yeast, capable of expressing XI. In batch runs, GSE16-T18 (T18) yeast encapsulated in alginate gel was capable to ferment xylose efficiently, consuming 40 g/L of xylose in 4 h and producing 14.4 g/L of ethanol, with yield of 0.422 g/g and productivity of 3.61 g/L.h. Calcium alginate gel encapsulation also contributed to protect yeast from the action of inhibitors, such as acetic acid. The encapsulated T18 was able to perform 10 consecutive cycles in repeated batch (yeast extract-peptone medium with 40 g/L of xylose), keeping the same productivity and high yields. It also fermented efficiently sugarcane bagasse hydrolysate, containing 60 g/L of fermentable sugars and high grade of inhibitors. The modified yeast to be more tolerant to acetic acid, GSE16-T18 HAA1, was also studied, exhibiting superior performance in comparison to T18 for hydrolysate fermentations. Continuous experiments were conducted in a fixed bed reactor using the T18-HAA1 yeast immobilized, with different xylose concentrations (40, 60, 80 and 120 g/L) in the feed medium. The reactor was operated up to 15 days, without bacterial contamination, with yield of 0.45 g/g, productivity of 4.8 g/L.h and selectivity of 31 gethanol/gxylitol (60 g/L of xylose in the feed). For the concentrations higher than 60 g/L, the conversion decreased after 4 days of continuous operation, indicating loss of cell viability due to hazardous effect of ethanol when present at 30 g/L or more, as well as limitation of oxygen and nutrients in the system.
Keywords: Bioetanol; Hemicelulose; Imobilização enzimática; Imobilização celular; Saccharomyces cerevisiae recombinante; Hidrólise, isomerização e fermentação simultâneas (SHIF); Bioethanol; Hemicellulose; Enzyme immobilization; Cell immobilization; Recombinant Saccharomyces cerevisiae; Simultaneous hydrolysis isomerization and fermentation (SHIF); ENGENHARIAS::ENGENHARIA QUIMICA